Coronary artery bypass surgery in British Indo-Asian and white caucasian individuals: is ethnicity a predictor of poorer outcome?. (22nd September 2015) - Hadjinikolaou, L; Iacona, GM; Spyt, T; Samani, NJ
Abstract : Objective: Previous studies have suggested that south Asian ethnicity is a predictor of poorer outcome after coronary artery bypass grafting (CABG). Our aim was to identify potential reasons for the higher postoperative mortality in south Asian patients and investigate the effect of ethnicity on the medium-term survival following CABG. Population: All individuals undergoing isolated CABG in the period April 2002–September 2007. In total, there were 2897 subjects (2623 white subjects; 274 south Asian subjects). Design: This is an observational study. Main outcome measures are survival at 30 days and survival up to 5 years (median 2.7 years). Results: South Asian subjects undergoing CABG were younger (62 ± 9 vs 66 ± 9 years, p<0.001), less obese (body mass index 26 ± 4 vs 28 ± 4 kg/m 2, p<0.001) and had a higher prevalence of diabetes mellitus (58% vs 33%, p<0.001) compared with white subjects. 30-Day mortality was higher in south Asian subjects (2.6% vs 1.0%, p = 0.02). This is most likely due to the higher proportion of subjects with diabetes in this group. South Asian subjects with diabetes had a significantly higher postoperative mortality compared with white caucasian subjects with diabetes (3.8% vs 1.4%, p = 0.01) and any other subgroup, including those without diabetes, south Asians without diabetes. Logistic multiple regression analysis on the predictors of the 30-day mortality following CABG showed that mortality was significantly predicted by the logistic Euroscore and the presence of diabetes. Allowing for diabetes, south Asian ethnicity by itself did not affect 30-day mortality. Although the higher incidence of diabetes mellitus in south Asian patients is well known, the reason for the higher postoperative mortality in south Asian patients with diabetes is not clear. Medium-term survival following CABG did not differ between white caucasian and south Asian patients. Multiple regression analysis showed that the risk factors for medium-term mortality were old age, logistic Euroscore, urgency and diabetes, not ethnicity. Notably, south Asian patients without diabetes had almost identical postoperative mortality and 5-year survival compared with the white caucasian patients without diabetes (fig 1). Similarly, life expectancy did not differ between white caucasian and south Asian patients without diabetes. However, south Asians with diabetes had a worse life expectancy compared with white subjects with diabetes (fig 2). The onset of diabetes at a younger age, the more aggressive nature of the disease and the need for CABG at a younger age may contribute to the lower life expectancy of south Asian patients with diabetes. Conclusions: The higher early postoperative mortality observed in south Asian patients is related to the higher incidence of diabetes among them. South Asian patients with diabetes have a significantly higher postoperative mortality and worse overall life expectancy. Ethnicity per se is not an independent predictor of short or medium-term survival after CABG.